Rancangan Desain Pembelajaran Science, Technology, Enggineering and Mathematic untuk Meningkatkan Kemampuan Pemecahan Masalah Matematis Siswa - Neni Widias; Hakim Lukman El (Pendidikan Matematika FKIP Universitas Mataram, 2022)
One of the mathematical abilities that must be mastered by students is the ability to solve mathematical problems. If students have good mathematical problem solving skills, students not only memorize the concepts that have been taught but can also be applied in everyday life and other disciplines. Therefore, it is important for a student to improve his mathematical problem solving abilities. But in learning, the teacher often gives questions that are routine which causes the students' mathematical problem solving ability to be low. When students are asked to work on non-routine questions, students find it difficult. Therefore, the authors designed a learning design that allows students to apply mathematical concepts to other disciplines and everyday life. The design of learning design chosen by the author is to use the Science, Technology, Engineering, and Mathematics (STEM) learning approach which is expected to use the STEM approach to improve students' mathematical problem solving abilities.